KARAKTERISASI MORFOLOGI SPORA FUNGI MIKORIZA ARBUSKULA PADA DAERAH PERAKARAN BEBERAPA TANAMAN INDUSTRI DI LAHAN PERTANIAN DESA TINDOLI - Mandjarara, Karmen; Pata’dungan, Yosep Soge; Thaha, Abd. Rahim (AGROTEKBIS, 2019)
The aim of this research is to know the existence and number of spores and to know the morphological characteristics of arbuscular mycorrhizal fungi (AMF). This research was conducted from November 2017 until February 2018. The method used in this research is explorative descriptive method by puporsive sampling for soil sampling. The results showed that the highest spore populations found in rhizosphere of pepper plants with the number of 204 per 10 grams of soil then the second high spore population that is in the soil samples of hazelnut with the number of 147 spores per 10 grams of soil, then the highest number of spores later on the sample of mangoes with the number of spores 122 per 10 grams soil, next to the clove plant soil samples with the number of spores 101 per 10 grams of soil, then in soil samples, and the lowest number of spores found pepper area rooting vanilla plants with the number of spores 49 per 10 grams of soil. Characteristics of spore morphology of genus glomus found are round to oval, spore color ranging from clear, yellow to brown while the genus gigaspora found round-shaped, large yellow.